(untitled) (Academia Journal of Medicine, 2025)
Chronic Kidney Disease (CKD) is a progressive disorder affecting kidney structure and function, often complicated by Type 2 Diabetes Mellitus (T2DM) and hypertension. Early stage CKD is frequently asymptomatic, and management can be challenging, particularly in resource-limited settings due to high costs and limited accessibility of conventional therapies. This case report presents a 67-year-old male patient with CKD, T2DM, and hypertension, treated at Jeena Sikho Lifecare Limited Hospital, Derabassi, India, using a personalized Ayurvedic regimen combined with Panchakarma therapies. Following 12 days of inpatient treatment, the patient demonstrated marked clinical improvements: drowsiness, pedal oedema, eye vision and urine got better. Vital parameters showed gradual stabilization, with body weight decreasing from 83 kg to 76 kg and blood pressure stabilizing from highs of 180/90 mmHg to 120/80 mmHg. Laboratory investigations indicated significant improvements, with hemoglobin increasing from 7.3 gm/dL to 10.0 gm/dL, urea decreasing from 280.12 mg/dL to 100 mg/dL, creatinine declining from 6.10 mg/ dL to 4.5 mg/dL, and total RBC count increasing from 2.61 Mill/Cumm to 3.54 Mill/ Cumm. Uric acid stabilized at 7.1 mg/dL. Renal function assessed by GFR improved, with global GFR from 14.2 to 19.8 ml/min. This case highlights the potential of Ayurveda as an effective, accessible, and affordable approach for managing CKD Stage IV and associated comorbidities, demonstrating improvements in symptoms, vitals, laboratory parameters, and kidney function over a short inpatient treatment period.